2004
DOI: 10.1095/biolreprod.103.025346
|View full text |Cite
|
Sign up to set email alerts
|

The Acroplaxome Is the Docking Site of Golgi-Derived Myosin Va/Rab27a/b-Containing Proacrosomal Vesicles in Wild-Type and Hrb Mutant Mouse Spermatids1

Abstract: Acrosome biogenesis involves the transport and fusion of Golgi-derived proacrosomal vesicles along the acroplaxome, an F-actin/keratin 5-containing cytoskeletal plate anchored to the spermatid nucleus. A significant issue is whether the acroplaxome develops in acrosomeless mutant mice. Male mice with a Hrb null mutation are infertile and both spermatids and sperm are round-headed and lack an acrosome. Hrb, a protein that contains several NPF motifs (Asn-Pro-Phe) and interacts with proteins with Eps15 homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 22 publications
3
94
0
1
Order By: Relevance
“…In step 1-8 spermatids, the nuclear shape was round and not deformed yet, but fragmented acrosome-like vesicles, previously called pseudoacrosomes (Kierszenbaum et al, 2004), were found near the nucleus in appreciable sizes (Fig.1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In step 1-8 spermatids, the nuclear shape was round and not deformed yet, but fragmented acrosome-like vesicles, previously called pseudoacrosomes (Kierszenbaum et al, 2004), were found near the nucleus in appreciable sizes (Fig.1).…”
Section: Resultsmentioning
confidence: 92%
“…The marginal ring has recently been characterized and is thought to be essential for the acrosomal vesicles to be anchored to the inner membrane of nuclear envelope or nuclear lamina (Kierszenbaum et al, 2004). The marginal ring is generally formed at the descending edge of the acrosome, and consists of F-actin and keratin 5 in addition to some other unknown molecule(s) in wild-type spermatids ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, hRIP activity is highly specific and is required for the proper cytoplasmic localization of RRE-containing RNAs but not typical cellular mRNAs (20). Second, hRIP is localized at the perinuclear region, where the machinery for vesicular trafficking is situated (35,41,42). Third, hRIP contains an N-terminal zinc finger motif that shares a high degree of sequence identity with the catalytic domain of ADP-ribosylation factor GTPase-activating proteins (Arf GAPs) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that the zinc finger motif of hRIP, and possibly a catalytic activity similar to that of Arf GAPs, may mediate release of Rev-RNA complexes from the perinuclear region. Fourth, hRIP is required for correct localization and function of acrosomal components during spermatogenesis, a process that depends upon vesicular trafficking (41,42). Finally, recent studies have shown that murine leukemia virus RNA is transported to the plasma membrane through a vesicular trafficking pathway (45).…”
Section: Discussionmentioning
confidence: 99%